Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to show that $H_D = -i\boldsymbol{\alpha}.\nabla+\beta m$ is hermitian.

Its given that $$ \gamma^{0\dagger}=\gamma^0 $$ $$ \boldsymbol\gamma^\dagger=-\boldsymbol\gamma $$

What i've done is: $$ H_D^\dagger = +i\boldsymbol\alpha^\dagger.\nabla+\beta^\dagger m $$ $$ =+i(\gamma^0\boldsymbol\gamma)^\dagger.\nabla+\beta m $$ $$ =+i(\boldsymbol\gamma^\dagger\gamma^{0\dagger}).\nabla+\beta m $$ $$=-i(\boldsymbol\gamma\gamma^0).\nabla+\beta m $$

Well clearly i'm doing somthing wrong because $\boldsymbol\gamma\gamma^0\neq\gamma^0\boldsymbol\gamma$

share|cite|improve this question
$\nabla^\dagger = - \nabla$ and $\bf{\gamma} \gamma^0 = - \gamma^0 \bf{\gamma}$ – Prahar Jun 12 '13 at 19:03
why $\nabla^\dagger=-\nabla$ @Prahar – Aftnix Jun 12 '13 at 19:12
Please give in a answer form so that i can accept it. – Aftnix Jun 12 '13 at 19:13
The operator $p = i \nabla$ is hermitian (this is the observable momentum), so $p = p^\dagger$, so $(i \nabla)^\dagger = (i \nabla)$. So there is an sign error in the first line. At the end, you have to add a step, that is $\gamma \gamma_0 = -\gamma_0 \gamma = \alpha$ – Trimok Jun 12 '13 at 19:34
up vote 5 down vote accepted

So the key is to understand that $\nabla^\dagger = - \nabla$. To see why this should be true, we go back to the definition of the adjoint of an operator, namely $$\left< \phi \right|\left. A \psi \right> = \left< A^\dagger\phi \right|\left. \psi \right> \implies \int d^dx \phi(x)^* {\hat A} \psi(x) = \int d^d x \left( {\hat A}^\dagger \phi(x) \right)^* \psi(x)$$

In particular, for the differential operator

$$\int \phi^* \nabla \psi = - \int \nabla \phi^* \psi = \int \left( - \nabla \phi \right)^* \psi \implies \nabla^\dagger = - \nabla$$

share|cite|improve this answer
Have you done integration by parts in $\int\phi^*\nabla\psi=-\int\nabla\phi^*\psi$? – Aftnix Jun 12 '13 at 19:50
Yes. I have assumed that the boundary term drops out. – Prahar Jun 12 '13 at 19:59

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.